Pengaruh Pemasaran Media Sosial Influencer Terhadap Minat Pembelian Dengan Keterlibatan Pelanggan Dan Citra Merek Sebagai Variabel Intervening - Adryan, Ravi Nuki; Mahmud, Mahmud; Setyahuni, Suhita Whini; Setiawan, Aries (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The purpose of this study is to analyze the influence of Social Media influencers, Consumer involvement and Brand Image on Consumer Purchase Intention on Kanky shoe products. The population of this study were consumers who had purchased Kanky products with a sample of 110 consumers. The method used in this research is quantitative. The sampling technique used purposive sampling, the type of data used is primary data. The data collection method used a questionnaire via Google Form, data analysis using Smart PLS. The results of the data processing concluded that Social Media Influencers did not have a significant effect on Purchase Intention of Kanky Shoe products. Social Media Influencers through brand image and Social Media Influencers through Customer Involvement have a significant influence on purchasing decisions for Kanky shoe products. The results of the study showed that brand image and customer involvement have a significant influence on Purchase Intention. But brand image does not have a significant effect on customer involvement.Keywords : social media influencer marketing, consumer engagement, brand image, purchase intention